2023
DOI: 10.1039/d2cc05722k
|View full text |Cite
|
Sign up to set email alerts
|

A dual-functional Bi-doped Co3O4 nanosheet array towards high efficiency 5-hydroxymethylfurfural oxidation and hydrogen production

Abstract: Here we report that Bi-doped Co3O4 nanosheets array grown on Ni foam can selectively catalyze the HMF-to-FDCA oxidation at ambient conditions. The catalyst shows a Faradaic efficiency of 97.7%, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…The three types of RFB systems are summarized in Table 3. 90–99 Presently, the bromine and iodine-positive electrodes appear to be more promising, owing to their high solubilities and kinetic reversibility as common electrode materials (CFs or GFs). 100–106…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three types of RFB systems are summarized in Table 3. 90–99 Presently, the bromine and iodine-positive electrodes appear to be more promising, owing to their high solubilities and kinetic reversibility as common electrode materials (CFs or GFs). 100–106…”
Section: Discussionmentioning
confidence: 99%
“…The three types RFB systems are summarized in Table 3. [90][91][92][93][94][95][96][97][98][99] Presently, the bromine and iodine-positive electrodes appear to be more promising, owing to their high solubilities and kinetic reversibility as common electrode materials (CFs or GFs). [100][101][102][103][104][105][106] So far, the ZBRFB has already been applied to LSESA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the attention on the CO 2 RR has extended to the catalytic environment, as the catalytic activity can be modulated by altering the structural parameters of the catalyst (solid)-electrolyte (liquid)-molecular reactant (gas) three-phase interface [ 144 , 145 , 146 ]. Some advances have been realized in these interfacial modulation studies, wherein it was discovered that controlling the proton supply or CO 2 supply can effectively inhibit the HER [ 147 , 148 ], electrodes with improved interfacial structures significantly improve selectivity and partial current density at relatively low overpotentials in H-type electrolytic cells [ 149 , 150 ], and membrane reactors and microfluidic reactors (flow cells) can achieve higher current densities [ 151 , 152 ]. Modification of the catalyst-electrolyte interface region also includes the addition of external molecules (or polymers), changes in electrolyte composition and concentration, the design of novel reactor and electrode structures, and a combination of these approaches, and these modification strategies can significantly affect the intrinsic and extrinsic catalytic activity of the catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…The electrocatalytic N 2 reduction reaction (NRR) driven by renewable electricity is regarded as an attractive alternative to the Harber-Bosch route because it can hydrogenate nitrogen molecules with protons and electrons at ambient conditions. [8][9][10][11][12][13][14][15][16][17] Up to now, noble metal-based materials, [18][19][20] carbon-based materials, [21,22] and single-atom catalysts [23,24] have been developed for catalyzing the NRR to generate NH 3 ; however, the inert chemical property of N 2 molecule makes the reported NH 3 yield rates all far lower than that of industrial-level demand. Recent advances have confirmed that the electrochemical NO reduction reaction (NORR) could deliver a higher NH 3 yield rate (> 200 μg h À 1 mg cat.…”
Section: Introductionmentioning
confidence: 99%